(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Anthrax is a fatal septicemic disease of warm-blooded animals including human and caused by Bacillus anthracis. Anthrax is common in farm ruminants, causes regular mortality and the disease is commonly prevented by using vaccine. The Sterne strain F-34 vaccine has been using in ruminants for more than five decades in Bangladesh but there is little work describing the efficacy of the vaccine in laboratory or farm animal’s. This study was aimed to evaluate efficacy of F-34 Sterne strain anthrax vaccine in mice model and isolate B. anthracis in culture from field outbreaks to identify level of protection in vaccinated mice. Anthrax vaccine containing F-34 Stern strain was obtained from Livestock Research Institute (LRI), Mohakhali, Dhaka. Group C and D female mice were immunized subcutaneously with 0.1ml of vaccine and Group A and B mice were served as non-immunized control. Polymerase chain reaction (PCR) technique was carried out to detect pX01 (210bp) and pX02 plasmid (1035bp) of B. anthracis from the field isolates, vaccine bacteria and challenged mice. Out of 13 field samples tested, B. anthracis was isolated from 05 cases. Following 6 months of immunization the Group B and Group D mice were challenged intraperitoneally with 2x105 colony forming unit (CFU) of virulent field isolate of B. anthracis (isolate of Shahjadpur Upazila, Sirajganj). The vaccine efficacy was evaluated in terms of anti-anthrax IgG antibodies responses in ELISA (A450±SD) and protection to challenge in vivo. The early anti-anthrax IgG antibody response was detected in Group C and D mice following week 2 of immunization (0.501±0.167) and reached its peak in study week 4 (1.237±0.257). A teadily higher level of anti-anthrax IgG antibody response was detected until 180 days of study (1.269±0.217, group average±SD). In vivo challenge to vaccinated mice with the virulent B. anthracis bacteria found to confer solid protection following six months of immunization. Non-immunized mice challenged with field isolate of B. anthracis succumbed to death within 18- 24hours of infection, showed characteristics lesions of anthrax including black berry jam spleen, wide spread congestion and hemorrhages and bleeding through natural opening after death. B. anthracis was re-isolated from the visceral organs of experimentally infected mice. This study provide evidence that the Sterne strain F-34 Anthrax vaccine is protective in mice model and generated higher level of anti-anthrax IgG antibody response until day 180 of immunization. It needs to study whether the vaccine is effective in farm animal model with longer duration. J Bangladesh Agril Univ 18(2): 405–414, 2020 https://doi.org/10.5455/JBAU.95978